ANALISIS KUALITAS ASAM PALMITAT 99,0% SEBAGAI BAHAN TAMBAHAN PAKAN MENURUT STANDAR GMP+FSA - Tambunan, Pravil Mistryanto; Sihotang, Supran Hidayat (LENVARI, 2025)
Palmitic acid is a saturated fatty acid widely used as a feed additive to increase energy density and support livestock performance. This study aims to analyze the quality of 99.0% Palmitic Acid product sourced from an oleochemical industry in North Sumatra and evaluate its compliance with the international GMP+ FSA (Feed Safety Assurance) certification standard. The analytical methods used include purity testing by Gas Chromatography (GC), moisture content test, acid value test, and contaminant testing (heavy metals and microbes). The results show that the analyzed product has an average purity of 99.3%, a moisture content of 0.1%, and an acid value of 205 mg KOH/g. All tested parameters met the stringent requirements set by the GMP+ FSA standard. It is concluded that this 99.0% Palmitic Acid product from the North Sumatran oleochemical industry is suitable and safe for use as a feed additive, thus can be recommended for application in the feed industry that prioritizes feed safety assurance and supports local resource potential.